Differential ubiquitin-proteasome and autophagy signaling following rotator cuff tears and suprascapular nerve injury - Joshi, Sunil K. (2013)
Previous studies have evaluated role of Akt/mTOR signaling in rotator cuff muscle atrophy and determined that there was differential in signaling following tendon transection (TT) and suprascapular nerve (SSN) denervation (DN), suggesting that atrophy following TT and DN was modulated by different protein degradation pathways. In this study, two muscle proteolytic systems that have been shown to be potent regulators of muscle atrophy in other injury models, the ubiquitin-proteasome pathway and autophagy, were evaluated following TT and DN. In addition to examining protein degradation, this study assessed protein synthesis rate following these two surgical models to understand how the balance between protein degradation and synthesis results in atrophy following rotator cuff injury. In contrast to the traditional theory that protein synthesis is decreased during muscle atrophy, this study suggests that protein synthesis is up-regulated in rotator cuff muscle atrophy following both surgical models. While the ubiquitin-proteasome pathway was a major contributor to the atrophy seen following DN, autophagy was a major contributor following TT. The findings of this study suggest that protein degradation is the primary factor contributing to atrophy following rotator cuff injury. However, different proteolytic pathways are activated if SSN injury is involved.